Donation after Circulatory Death Heart Transplantation: An Update of Current Practices and Outcomes. (July 2018) - Chew, Hong Chee; Connellan, Mark; Iyer, Arjun; Granger, Emily; Hayward, Christopher; Jabbour, Andrew; Jansz, Paul; Keogh, Anne; Kotlyar, Eugene; Spratt, Phillip; Macdonald, Peter; Dhital, Kumud
Abstract : Method: 17 DCD heart transplants were performed between July 2014 and October 2017. All hearts were retrieved using normothermic machine perfusion (NMP) according to local protocol. Donor information including cause of death, LV function at time of referral, and important time points during the withdrawal and retrieval process were collected. All hearts were reperfused and assessed using Transmedic OCS Heart™. Recipient data were collected and updated through follow up at the Heart Lung Clinic at St Vincent's Hospital, Sydney. The following outcomes were analysed: Survival, delayed graft function, ICU and Hospital length of stay (LOS), serial endomyocardial biopsy (EMBx) and echocardiogram results post-transplant. Results: Donor mean age was 30±6 years with baseline LV function of 61 ± 5%. There are 13:4 (M:F) donors and 11:6 recipients. Recipient baseline mean transpulmonary gradient was 8.4 ± 3mmHg with cardiac index of 1.7±0.42L/min/m2. Average time from withdrawal to asystole was 10 ± 4min, and warm ischaemic time (WIT) 23 ± 4 min. Time on NMP was 281 ± 72mins. Lactate results are presented below. 6 patients had delayed graft function requiring mechanical support using ECMO, and 1 patient had technical complication requiring return on bypass with resultant ECMO on subsequent weaning off bypass. All recipients however show normal graft function at 1 week post-transplant. Average ICU and hospital stay were 8±5 days and 25±13 days (n=16). All recipients are alive and demonstrate NYHA 1, and normal cardiac function on echocardiogram on most recent follow up, including 3 recipients > 3 years post-HTx. Conclusion: DCD outcomes to date are excellent despite high utilisation of ECMO for delayed graft function. Overall, DCD donors have contributed to an annual increase of 10-15% HTx activity in our centre. Figure. No caption available.